Model Marketing Strategy Voters In Political Novice PILGUB Province Lampung 2014 - dora rinova (Universitas Bandar Lampung (UBL), 2016)
This research using the theory hotchpotch marketing that is a collection of tools marketing tactical under control who integrated company to produce a response before long target market.The purpose of this research was aiming to compile and recommended strategy what shall in prioritize to into the delivery of campaign do social media, the print, electronic media, and media outdoor during the election campaigns the provincial governor lampung 2014.A method of descriptive in this research is the approach ahp ( analitycal hierarchy process ). The results of research obtained was several alternative strategies which: 1 melakukkan marketing activities by intense and serious through the outdoor , 2 ) performs activities marketing by intense and serious through the social network , 3 ) melakukkan marketing activities by intense and serious through the print , 4 ) make promotional programs dengaan in cooperation with electronic media of existing local at the in an intense manner and serious via electronic media .From a number of alternatives more will be given priority , is to do activities marketing by intense and serious through the print keywords: Political Marketing Mix.